Craniofacial Development - Chai, Yang; ScienceDirect eBooks (Waltham, MA : Academic Press is an imprint of Elsevier, 2015)
Craniofacial Development, the latest volume of Current Topics in Developmental Biology continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers research methods in Craniofacial Development, and includes sections on such topics as microRNAs in craniofacial development and epigenetic regulation in craniofacial development.
Text in English.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed November 24, 2015).
Elsevier
Keywords: Skull -- Growth; Facial bones -- Growth; Head -- Molecular aspects; MEDICAL -- Anatomy; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Electronic books